2010
DOI: 10.1523/jneurosci.4777-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Decaffeinated Coffee and Nicotine-Free Tobacco Provide Neuroprotection in Drosophila Models of Parkinson's Disease through an NRF2-Dependent Mechanism

Abstract: Epidemiological studies have revealed a significantly reduced risk of Parkinson's disease (PD) among coffee and tobacco users, although it is unclear whether these correlations reflect neuroprotective/symptomatic effects of these agents or preexisting differences in the brains of tobacco and coffee users. Here, we report that coffee and tobacco, but not caffeine or nicotine, are neuroprotective in fly PD models. We further report that decaffeinated coffee and nicotine-free tobacco are as neuroprotective as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
88
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 31 publications
5
88
1
1
Order By: Relevance
“…Our results indicate that caffeine is not the primary protective compound in aqueous coffee extracts, in agreement with the Drosophila studies examining the protective effects of coffee in PD models (Trinh et al 2010). We cannot exclude the possibility that the protective effects of coffee are due to changes in the E. coli food source used in these experiments, but this seems highly unlikely given the effects of coffee extracts in other systems, such as flies, Figure 5.-SKN-1 is required for coffee extract protection against Ab 42 -induced paralysis.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Our results indicate that caffeine is not the primary protective compound in aqueous coffee extracts, in agreement with the Drosophila studies examining the protective effects of coffee in PD models (Trinh et al 2010). We cannot exclude the possibility that the protective effects of coffee are due to changes in the E. coli food source used in these experiments, but this seems highly unlikely given the effects of coffee extracts in other systems, such as flies, Figure 5.-SKN-1 is required for coffee extract protection against Ab 42 -induced paralysis.…”
Section: Resultssupporting
confidence: 90%
“…Similarly, chemical or genetic activation of the Nrf2 pathway is protective in multiple Drosophila models of PD (Trinh et al 2008). Of perhaps greatest relevance to our C. elegans studies, coffee and tobacco extracts have recently been shown to be protective in Drosophila neurodegeneration models, and this protection is Nrf2 dependent (Trinh et al 2010). Our demonstration that coffee exposure protects against GFPTdegron, a model toxic aggregating protein not associated with a specific disease, further supports the generality of protection by Nrf2 activation.…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations